Managing Refugee Protection Crises: Policy Lessons from Economics and Political Science - Matti Sarvimäki (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2021)
We review and interpret research on the economic and political effects of receiving asylum seekers and refugees in developed countries, with a particular focus on the 2015 European refugee protection crisis and its aftermath. In the first part of the paper, we examine the consequences of receiving asylum seekers and refugees and identify two main findings. First, the reception of refugees is unlikely to generate large direct economic effects. Both labor market and fiscal consequences for host countries are likely to be relatively modest. Second, however, the broader political processes accompanying the reception and integration of refugees may give rise to indirect yet larger economic effects. Specifically, a growing body of work suggests that the arrival of asylum seekers and refugees can fuel the rise of anti-immigrant populist parties, which may lead to the adoption of economically and politically isolationist policies. Yet, these political effects are not inevitable and occur only under certain conditions. In the second part of the paper, we discuss the conditions under which these effects are less likely to occur. We argue that refugees' effective integration along relevant linguistic, economic, and legal dimensions, an allocation of asylum seekers that is perceived as 'fair' by the host society, and meaningful contact between locals and newly arrived refugees have the potential to mitigate the political and indirect economic risks.
Keywords: 330